Sweden : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the high household savings in Sweden. Preliminary evidence suggests that the large increase in savings after the financial crisis may reflect the rising cost of elder care. Econometric analysis appears to confirm anecdotal explanations that extended life expectancy and a preference for higher-quality residential care have contributed to higher savings. Further analysis using more granular data is needed to test alternative hypotheses for the rise in household savings. Anecdotal reports also indicate that parental assistance in young people's home purchases could be behind the increased saving and serves as an additional bequest motive. Investigating this possibility would benefit significantly from household level data.